Population-based prevalence study of common congenital malformations of the alimentary tract and abdominal wall in Thailand: a study using data from the National Health Security Office - Surasak Sangkhathat; Kulpreeya Sirichamratsakul; Wison Laochareonsuk; Komwit Surachat (BMJ Publishing Group, 2023)
Background The study aimed to estimate the prevalence of major congenital anomalies of the alimentary system and the abdominal wall in Thailand using a nationwide hospital discharge database from the National Health Security Office (2017-2020).Methods The study extracted data from records with International Classification of Diseases-10 (ICD-10) codes related to esophageal malformation (ESO), congenital duodenal obstruction (CDO), jejunoileal atresia (INTES), Hirschsprung's disease (HSCR), anorectal malformation (ARM), abdominal wall defects (omphalocele (OMP) and gastroschisis (GAS)), and diaphragmatic hernia from the database with patient age selection set to less than 1 year.Results A total of 2539 matched ICD-10 records were found in 2376 individuals over the 4-year study period. Concerning foregut anomalies, the prevalence of ESO was 0.88/10 000 births, while that of CDO was 0.54/10 000 births. The prevalence figures of INTES, HSCR, and ARM were 0.44, 4.69, and 2.57 cases per 10 000 births, respectively. For abdominal wall defects, the prevalences of OMP and GAS were 0.25 and 0.61 cases/10 000 births, respectively. The mortality in our cases was 7.1%, and survival analysis found that associated cardiac defects had a statistically significant influence on survival in most anomalies studied. In HSCR, both Down syndrome (DS) (hazard ratio (HR)=7.57, 95% confidence interval (CI)=4.12 to 13.91, p<0.001) and cardiac defects (HR=5.82, 95% CI=2.85 to 11.92, p<0.001) were significantly associated with poorer survival outcomes. However, only DS (adjusted HR=5.55, 95% CI=2.63 to 11.75, p<0.001) independently predicted worse outcomes by multivariable analysis.Conclusions Our analysis of the hospital discharge database found that the prevalence of gastrointestinal anomalies in Thailand was lower than that reported in other countries, except for HSCR and anorectal malformations. Associated Down syndrome and cardiac defects influence the survival outcomes of these anomalies.